Antimatter Technology: The Bridge between Science and Religion toward Universe Creation Theory Illustrated in Dan Brown’s Angels and Demons - Samanik Samanik; Fita Lianasari (TEKNOSASTIK, 2016)
Science deals with the study of nature, its forces, processes and development. It is based on the analysis of evidence, meanwhile religion deals with matters of faith. Some of the areas where science and religion overlap, and make conflicting claims, are Cosmology, geology, astronomy, etc. The analysis will be focused on describing the way the antimatter technology bridges the deep rift between science and religion related to the theory of universe creation. through Angel and Demon, Dan Brown wants to potrays the conflict between science and religion  century related to the universe creation theory. Though the story is focussed on the assasination of Vetra and four preferity cardinal by illuminati which steal antimatter technology from CERN, the Antimatter technology as the bridge between science and religion toward universe creation theory plays a fundamental part in the novel. In addition, by depicting the case of Antimatter technology as the bridge between science and religion toward universe creation theory in Angel and Demon, Dan Brown as the author wants to show the readers how the antimatter can brigde the perception between science and religion in universe creation.